1987
DOI: 10.1079/bjn19870094
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the solid phase of rumen digesta in the interaction between copper, molybdenum and sulphur in sheep

Abstract: 1. Merino sheep fed on a diet of chopped wheaten hay, chopped lucerne (Medicago saliva) hay and oat grain were the source of rumen contents for the study. The diet contained (mg/kg dry weight) 3.3 copper, 024 molybdenum and 2-8 sulphur. The effects of adding between 5 and 25 mg Mo/kg as ammonium molybdate (AM) or tetrathiomolybdate (TTM) on the distribution and forms of Cu and Mo in rumen contents were investigated in vivo and in vitro. 2.Approximately 88 YO of the Cu and 94% of the Mo in rumen contents were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Já em relação aos teores hepáticos e considerando os dados de grupos controle de diferentes delineamentos experimentais, foi possível encontrar uma amplitude de valores, que variaram de 1,80mg/kg (Allen & Gawthorne 1987, 2,9mg/kg (Van Ryssen & Stielau 1981, 3,62mg/kg (Antonelli 2007), 3,80mg/kg (Jones et al 1984), 5,88mg/kg (Pott et al 1999) e 8,55mg/kg (Gonzáles et al 2000. Tais valores médios da concentração hepática de Mo estão abaixo dos encontrados nos animais deste estudo, porém próximos aos encontrados por Pott et al (1999) e Van Ryssen & Stielau (1980.…”
Section: Discussionunclassified
“…Já em relação aos teores hepáticos e considerando os dados de grupos controle de diferentes delineamentos experimentais, foi possível encontrar uma amplitude de valores, que variaram de 1,80mg/kg (Allen & Gawthorne 1987, 2,9mg/kg (Van Ryssen & Stielau 1981, 3,62mg/kg (Antonelli 2007), 3,80mg/kg (Jones et al 1984), 5,88mg/kg (Pott et al 1999) e 8,55mg/kg (Gonzáles et al 2000. Tais valores médios da concentração hepática de Mo estão abaixo dos encontrados nos animais deste estudo, porém próximos aos encontrados por Pott et al (1999) e Van Ryssen & Stielau (1980.…”
Section: Discussionunclassified
“…In the present study, the increased protozoan abundance was observed after the highest dose of boric acid was added into diet, which could result in the reduction of ammonia utilizing bacteria. Since trace minerals form the complexes with protozoa and bacteria (Allen and Gawthornet, 1987), this form could be effective on bioactivity and metabolism by evaluating the degradation. However, further studies are needed to evaluate the effect of boron on the degradation of nutrients, such as fibre and crude protein, in rumen fluid both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Some trace minerals such as molybdenum and copper form complexes with solid rumen digesta including bacteria and protozoa (Allen and Gawthornet, 1987;Spears, 2003). Having this in mind, we hypothesized that the boron as a trace mineral might improve rumen microbial fermentation and protozoa abundance.…”
mentioning
confidence: 99%
“…Although forage S was not analyzed as part of this experiment, historical S concentrations on the sites, taken over several years, were only 0.01% to 0.1%. Sulfur is a critical part of the Cu-Mo interaction, 1,9,11,21 and it is possible that if forage S was significantly greater Mo effects would have been seen in Group III.…”
Section: Groupmentioning
confidence: 99%
“…2,4,10 Sulfur (S) potentiates most, if not all, of the effects of Mo in ruminants. Sulfide, which is formed in the rumen, displaces the oxygen in molybdate, forming various thiomolybdates that react with Cu at several levels, reducing both the dietary uptake 1 and biological availability of Cu to the cell. 9,19 The ratio of Cu, Mo, and S in the diet is critical to the Cu-Mo-S interaction and thus toxicity.…”
Section: Introductionmentioning
confidence: 99%